Infants' Perception of Intonation: Is It a Statement or a Question?. (1st October 2013) - Frota, Sonia; Butler, Joseph; Vigário, Marina
<x xml:space="preserve">Abstract</x> The ability to distinguish phonetic variations in speech that are relevant to meaning is essential for infants' language development. Previous studies into the acquisition of prosodic categories have focused on lexical stress, lexical pitch accent, or lexical tone. However, very little is known about the developmental course of infants' perception of linguistic intonation. In this study, we investigate infants' perception of the correlates of the statement/yes–no question contrast in a language that marks this sentence type distinction only by prosodic means, European Portuguese (EP). Using a modified version of the visual habituation paradigm, EP‐learning infants at 5–6 and 8–9 months were able to successfully discriminate segmentally varied, single‐prosodic word intonational phrases presented with statement or yes–no question intonation, demonstrating that they are sensitive to the prosodic cues marking this distinction as early as 5 months and maintain this sensitivity throughout the first year. These results suggest the presence of precocious discrimination abilities for intonation across segmental variation, similarly to previous reports for lexical pitch accent, but unlike previous findings for word stress.